2004
DOI: 10.1523/jneurosci.1067-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of α5-GABAAReceptors for the Development of Tolerance to the Sedative Action of Diazepam in Mice

Abstract: Despite its pharmacological relevance, the mechanism of the development of tolerance to the action of benzodiazepines is essentially unknown. The acute sedative action of diazepam is mediated via ␣ 1 -GABA A receptors. Therefore, we tested whether chronic activation of these receptors by diazepam is sufficient to induce tolerance to its sedative action. Knock-in mice, in which the ␣ 1 -, ␣ 2 -, ␣ 3 -, or ␣ 5 -GABA A receptors had been rendered insensitive to diazepam by histidine-arginine point mutation, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 35 publications
1
80
0
1
Order By: Relevance
“…There exist data that support the possibility of substantial motor manifestations of a5-containing GABA A receptor modulation, besides the indirect consequences brought on by the effects on learning and memory processes, where pertinent (Collinson et al, 2002;Crestani et al, 2002). Somatic and preganglionic motoneurons in the spinal cord exhibit a moderate-to-strong staining for the a5 subunit (Bohlhalter et al, 1996), whereas the knock-in mice harboring the a5 subunit insensitive to diazepam are refractory to development of tolerance to the sedative effect of diazepam dosed subchronically, presumably due to a downregulation of a5 subunits in the dentate gyrus (van Rijnsoever et al, 2004). Hence, we hypothesize that any locomotor activity changes induced by ligands possessing a substantial a5-efficacy may be, at least partly, contributed by modulation at GABA A receptors containing this subunit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exist data that support the possibility of substantial motor manifestations of a5-containing GABA A receptor modulation, besides the indirect consequences brought on by the effects on learning and memory processes, where pertinent (Collinson et al, 2002;Crestani et al, 2002). Somatic and preganglionic motoneurons in the spinal cord exhibit a moderate-to-strong staining for the a5 subunit (Bohlhalter et al, 1996), whereas the knock-in mice harboring the a5 subunit insensitive to diazepam are refractory to development of tolerance to the sedative effect of diazepam dosed subchronically, presumably due to a downregulation of a5 subunits in the dentate gyrus (van Rijnsoever et al, 2004). Hence, we hypothesize that any locomotor activity changes induced by ligands possessing a substantial a5-efficacy may be, at least partly, contributed by modulation at GABA A receptors containing this subunit.…”
Section: Discussionmentioning
confidence: 99%
“…In the spinal cord, somatic and preganglionic motoneurons (lamina IX and lateral cell column) exhibited a moderate to strong staining for the a5 subunit (Bohlhalter et al, 1996). Knock-in mice with the GABA A receptor a5 subunit rendered insensitive to diazepam were refractory to development of tolerance to the sedative effect of diazepam dosed subchronically (van Rijnsoever et al, 2004). These two sets of evidence indicate that the motor influence of a5-GABA A receptor modulation, if present, is not necessarily an indirect consequence of the established effects on learning and memory processes (Collinson et al, 2002;Crestani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, alpha5-GABA A receptors were insensitive and developed tolerance to the sedative actions of benzodiazepines. [21][22][23] Verkuyl et al 24) reported that expression of alpha5, not alpha1-GABA A receptors was increased in patients with hyperfunctional HPA axes. Therefore the absence of a flunitrazepam-induced hypnotic effect may be the result of tolerance developed by upregulation of alpha5-GABA A receptors in ACTH-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…The sedative effects of diazepam are mediated via a1-GABA A receptors in the brain [22,23] , and the minimum plasma concentration of diazepam to yield sedative effects is more than 300 ng/mL to 400 ng/mL [18,19] . The pharmacokinetics of diazepam are affected by age [24,25] , gender [26] , obesity [26] , liver disease [27] and CYP2C19 genotype status [5][6][7][8][9] .…”
Section: Discussionmentioning
confidence: 99%